PENGEMBANGAN MEDIA ANIMASI DONGENG UNTUK PEMBELAJARAN MENYIMAK CERITA DI KELAS III - Alwini, Selin Nadia (FKIP Unirow Tuban, 2022)
Abstract This research is motivated because there is saturation of students in listening to the contents of story texts, such as fairy tales. In the learning that has been carried out, the use of technology media has not been maximized, the teacher still looks dominant with the lecture method, so that learning is not optimal. Students need an alternative to make it easier for students to understand fairy tales. The solution that can be offered by the author is the development of existing media, namely animated videos to improve learning to listen to fairy tales for third grade students. The purpose of this study was to develop and test the feasibility and effectiveness of animated videos as learning media to improve the understanding of third grade elementary school students in understanding fairy tales. The data was obtained using the Research and Development (R & D) method, which is a method of developing or perfecting a product to test the effectiveness of a product that has been developed through several stages and can be accounted for. Then for the development design model, using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and the data collection instrument by distributing questionnaires, interviews, and observations. Based on the results of observations, it can be concluded that the students' responses were very good and they stated that learning to listen to fairy tales using animated video media greatly facilitated them in understanding the contents of the stories from the fairy tales. Keywords: Observe Attentively, Fairy Tale, Animated Videos, 3rd Grade Elementary School Student